Writing, Collaborating, and Expressing: Drama as a Means of Strengthening Social and Aesthetic Competence - Tato Nuryanto; Agus Nuryatin; Yusro Edy Nugroho; Indrya Mulyaningsih (Universitas Muhammadiyah Malang, 2025)
The background of this research is based on the limitations of conventional teaching methods that do not involve students optimally, so the potential of drama as a holistic learning tool has not been optimally developed. This study aims to integrate a collaborative drama scriptwriting approach into the Drama Appreciation course. This quantitative research uses a case study approach involving 95 Indonesian Language Study Program students. Data were collected through observation, interviews, and document analysis, in drama scripts, reflection journals, and discussion recordings. The study results showed a significant increase in social competencies, including teamwork, empathy, and communication. In the aesthetic aspect, there was an increase in creativity and language sensitivity. The results of the lecturer's evaluation showed that the script had depth of theme and originality. However, there were obstacles such as difficulty managing time and limited practice space. This research provides a theoretical contribution by enriching the study of drama pedagogy through a collaborative writing approach, as well as a practical contribution in the form of an innovative learning model that can be adopted in the curriculum.